Adult Male’s Penile Size Measurement and Its Affecting Factors - Mikhael San Putra Wijanarko; Cathelin Stella; Gian Oktavianto (Indonesian Andrology and Biomedical Journal, 2021)
Background: In the general population, it is estimated that 91% of adult males perceive their penile size to be smaller than average. Concern about penile size can affect one’s self-esteem, which then affects its sexual function, satisfaction, as well as physical and mental health. Therefore, accurate penile measurements are needed for clinical and academic purposes. Reviews: Measurement of penile size can be performed in an erect, stretched, even flaccid condition. However, from various researches, there is no standardization of such a measurement method. Various researches have carried out average penile measurement but many factors can affect these results such as race, genital conditions, systemic diseases, surgical procedures, and aging.  Summary: There is no internationally agreed way of measuring an adult male's penis and many other factors can make the results of penile measurements vary. Proper measurement and finding out the right average of penile size in adult male with regard to other affecting factors, will be indispensable for both clinical and academic purposes.